State, market and society: The development of Ikat textile value chains among the Iban of Sarawak, Malaysia / Wong Pui Yi - Wong , Pui Yi (2020)
Studies about the developmental state have focused on the role of the state in guiding a rapidly industrialising economy, by creating a nexus between the state and business, primarily large enterprises. There is no study within the literature on the role of state-society relations in nurturing community-based rural enterprises. This thesis examines the commercial development of handwoven ikat textiles, a niche cottage industry promoted by the state to preserve cultural heritage and to alleviate poverty. This study expands the developmentalist framework, which focuses on public policy outcomes and economic performance as contingent on the configurations of state agencies, national goals and political power, by incorporating value chain concepts to better analyse market and social logics that drive economic development. The overall aim of this study is to shed light on how the developmentalist and value chains frameworks enhance the understanding of the Malaysian (and Sarawakian) developmentalist state in the context of a rural cottage industry. The three key objectives are: To examine the nature of the federal and Sarawak governments; to analyse the roles played by market and societal actors and how they interacted with state actors; and to assess the challenges faced in the commercial development of ikat textiles in Sarawak. Qualitative data was collected through semi-structured, in-depth interviews with 119 informants comprising state actors and non-state actors involved in value chains, selected in a non-random manner. The Malaysian development model has been both developmental and clientelist; the needs of political survival and power asymmetries shape developmental outcomes even at this small scale of production in Sarawak. The development of ikat weaving in Sarawak is underlined by the “embedded interdependence” of key state, market and societal actors. In the more developed value chains, power is concentrated in the hands of the key actors, namely the patrons who were either part of the state, or who had formed institutionalised alliances with the state. The power asymmetry in the value chains determined the form of governance and upgrading outcomes. The embedded interdependence of the key actors enabled them to elicit the cooperation of the weavers to engage in value chain upgrading, while the captive form of value chain governance allowed the patrons to dictate the weaving process and products to meet market demands. However, the clientelist and exclusive nature of patron-weaver ties have also constrained the viability of the cottage industry. State institutions and CSOs have key roles to play in facilitating collective action models that can better empower communities. As enterprise development policies in Malaysia have been simultaneously interventionist and market-oriented in nature, even in a rural-based industry, state intervention has essentially focused on private sector development and the grooming of “lead firms” or patrons. While market-oriented, patron-led development has contributed to the growth of this industry, there is increasing disparities in income and opportunities among weaving communities, with many being left out. This thesis reveals the interdependent nature of state, market and society, and the importance of collaboration, consultation, and systemic reforms to ensure equitable and lasting development.